Aqueous defoaming composition and use thereof
Patent Information
- Application Number
- CN202580024697.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing defoaming compositions are unstable at high temperatures, and conventional anionic surfactants have poor compatibility with other components, resulting in decreased defoaming performance.
An aqueous defoaming composition is formed by combining anionic lignin-based additives with nonionic surfactants, containing 10-100% by weight of lignin-based additives to improve stability and defoaming efficiency.
It maintains stability during long-term storage at high temperatures, exhibits excellent defoaming properties, and has good compatibility with other components.
Smart Images

Figure CN123036148A_ABST
Abstract
Description
[0001] This invention relates to an aqueous defoaming composition and its use, according to the preamble of the appended independent claims.
[0002] Foaming is a problem in many industries that involve the handling and processing of water, aqueous solutions, and other aqueous liquids. To reduce foaming, it is common practice to add defoamers, defoaming agents, or defoaming compositions to the liquid phase where foaming occurs. Exemplary industry sectors that commonly use defoaming compositions include the manufacture of pulp, paper, paperboard, and textiles; the oil and mining industries; various water treatment processes; the manufacture of paints and coatings; food and beverage processing; and agriculture. The purpose of defoamers, defoaming agents, and defoaming compositions is to reduce foam formation or prevent it entirely. A variety of substances and compositions are known to reduce or prevent foam formation.
[0003] Defoaming compositions are typically in the form of oil / wax-in-water emulsions, stabilized by nonionic and anionic surfactants. The stability of the emulsion is crucial for the handling of the defoaming composition. Particularly important is the long-term stability of the emulsion at higher temperatures, as defoaming compositions are often exposed to elevated temperatures or other harsh conditions during transport from the manufacturing site to the application site and / or during possible storage between sites. Experience has shown that finding an anionic surfactant that is compatible with other components used in aqueous defoaming compositions while providing an ideal balance between emulsion stability and defoaming efficiency is quite challenging.
[0004] The anionic surfactants that can be used in defoaming compositions may be selected from, for example but not limited to, alkyl sulfonates, alkyl sulfates, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl ether sulfates, alkyl ether sulfonates, and soaps.
[0005] In practice, increasing the amount of surfactant, especially anionic surfactant, may sometimes improve emulsion stability, but it can also weaken defoaming performance due to over-stabilization of emulsion particles. Excessive stabilization hinders penetration into the foam film surface and effective spreading at the air-water interface. Therefore, defoaming compositions that offer both improved stability and more effective defoaming performance are needed. In particular, it is desirable to replace conventional anionic surfactants with superior anionic stabilizers that provide optimal performance.
[0006] At the same time, there is a general need to reduce the use of synthetic petroleum-based chemicals across all sectors of industry. This means there is a need for efficient, environmentally friendly, cost-effective, easy-to-prepare, and stable defoaming compositions.
[0007] The purpose of this invention is to reduce or even eliminate the aforementioned problems in the prior art.
[0008] Another object of the present invention is to provide a stable, preferably stable, defoaming composition that is even stable during long-term storage at elevated temperatures and has good defoaming efficiency.
[0009] Another object of the present invention is to provide an antifoaming composition derived from an increased content of renewable source components.
[0010] To achieve the above and other objectives, the present invention is characterized by the content presented in the characterizing portion of the appended independent claims. Some preferred embodiments of the invention are disclosed in the dependent claims presented below.
[0011] The embodiments mentioned herein relate to all aspects of the invention, namely the defoaming compositions and their uses, within the scope applicable, even though this is not always mentioned separately.
[0012] Typical aqueous defoaming compositions according to the present invention comprise
[0013] - At least one C10-C30 fatty alcohol,
[0014] - Nonionic surfactants,
[0015] - Optional wax and / or oil components, and
[0016] - Anionic lignin-based additives containing 10-100% by weight of lignin, calculated based on the total dry weight of the lignin-based additives.
[0017] Typical uses of the defoaming compositions according to the invention are in water treatment processes, the manufacture of fiber webs (such as paper, paperboard, etc.) or the manufacture of molded cellulose articles for preventing, controlling and / or reducing foam.
[0018] It has been surprisingly discovered that anionic lignin-based additives can be used as anionic stabilizers in defoaming compositions. The resulting defoaming compositions exhibit improved stability, especially at elevated temperatures (e.g., 35°C or higher). This means that the defoaming composition retains its performance even under suboptimal storage conditions between manufacturing and use. Unexpectedly, the defoaming compositions of the present invention can maintain their performance even when stored at elevated temperatures for extended periods (e.g., 10 days or longer, even 20 days or longer). Furthermore, the anionic lignin-based additive exhibits good compatibility with other common components used in the defoaming compositions. The defoaming compositions of the present invention also exhibit defoaming efficiencies at least equivalent to, and in most cases significantly superior to, those obtained using conventional prior art defoamers.
[0019] In the context of this application, the term "defoaming" refers to preventing, controlling, and / or reducing foam. The defoaming compositions of the present invention prevent, control, and / or reduce foam in industrial processes. Preventing foam is understood as not allowing foam to form, i.e., inhibiting the occurrence of foam. Controlling foam is understood as limiting the amount of foam to below a certain maximum or level of foam formation. Reducing foam is understood as reducing the amount of foam or completely eliminating foam after it has formed. The defoaming compositions of the present invention are used to treat easily foaming aqueous liquids (i.e., foaming water) and / or to treat foam-containing aqueous liquids.
[0020] Treating an aqueous liquid with a defoaming composition is achieved by adding the defoaming composition to the aqueous liquid, or vice versa. This addition can be continuous and / or at intervals, and can be discontinuous or at regular predetermined intervals. The amount of defoaming composition added, the time interval between additions, and / or the duration depend particularly on the amount of the aqueous liquid to be treated, the nature and composition of the aqueous liquid, the existing amount of foam, the foaming sensitivity of the aqueous liquid, and the industrial process itself.
[0021] The defoaming composition may have a total dry solids content of at least 10% by weight, preferably at least 13% by weight, and more preferably at least 15% by weight. For example, the defoaming composition may have a total dry solids content in the range of 10-50% by weight, preferably 13-30% by weight, and more preferably 15-25% by weight. Surprisingly, even with a relatively high total dry solids content, the defoaming composition still exhibits such good stability. It is speculated (without wanting to be bound by any theory) that even with a high total dry solids content, the anionic lignin-based additive can provide emulsion stability. A high dry solids content is advantageous because it minimizes the transport and storage of the solvent (water).
[0022] The defoaming composition of the present invention comprises an anionic lignin-based additive containing 10-100% by weight of lignin. This anionic lignin-based additive can be selected from various lignin-containing materials, which can be obtained directly as a byproduct of industrial processing of cellulosic materials (such as wood or pulp), or obtained through refining or upgrading such byproducts. Therefore, the anionic lignin-based additive may contain not only lignin but also other components, such as carbohydrates (e.g., hemicellulose), inorganic compounds, etc. According to one embodiment, the anionic lignin-based additive may have an ash content of 0.5-50% by weight, typically 2-40% by weight, based on dry matter. Here, ash content represents the amount of inorganic materials, such as calcium, potassium, and / or sodium compounds; iron, zinc, and / or manganese oxides; and any combination thereof. The ash content can be determined by burning 1 g of a dry lignin-based additive sample in a muffle furnace at 550°C for 5 hours, weighing the remaining ash, and then calculating the ash content of the sample.
[0023] According to one embodiment, the anionic lignin-based additive may be selected from lignin sulfonates, polymeric lignin, lignin-carbohydrate complexes, lignin obtained by extracting biomass (such as sawdust), or any mixture thereof. The anionic lignin-based additive may contain 20–100% by weight, preferably 65–99.9% by weight, more preferably 90–99% by weight, of lignin, calculated based on the total dry weight of the lignin-based additive. It is presumed that a high lignin content can particularly improve the stability of the defoaming composition of the present invention at high temperatures (35°C) and even for extended periods (>10 days), and enhance its defoaming efficiency.
[0024] The weight-average molecular weight of anionic lignin-based additives can range from 5,000 to 150,000 g / mol, preferably 7,000 to 130,000 g / mol, and more preferably 10,000 to 120,000 g / mol. It is speculated that the relatively large molecular size of lignin-based additives, expressed as molecular weight, has a positive impact on the stability and defoaming efficiency of defoaming compositions in emulsion form. It is speculated that once anionic lignin-based additives adsorb onto the oil / water interface in an emulsion-form defoaming composition, these additives will remain at these interfaces due to their molecular size and will not be easily desorbed. This minimizes the adsorption of anionic lignin-based additives at the air / water interface, providing good stability and minimal foam formation upon contact with foaming water.
[0025] The charge density of the anionic lignin-based additive can range from -3.0 meq / g to -0.05 meq / g, preferably from -2.5 meq / g to -0.5 meq / g, and more preferably from -2.0 meq / g to -1.0 meq / g, measured in a 200 ppm solution. All charge density values in this application are given on a dry matter basis and measured using a Mütek ParticleCharge Detector. It has been found that the charge density of the anionic lignin-based additive affects defoaming enhancement: the lower the charge density of the lignin-based additive, the better the defoaming effect.
[0026] According to one embodiment, the surface tension of the anionic lignin-based additive is in the range of 40–65 mN / m, preferably 43–60 mN / m, more preferably 43–55 mN / m, as measured from a 1% by weight solution of the anionic lignin-based additive using the Wilhelmy plate method.
[0027] The lignin-based additives used in this invention may also contain at least one, and typically multiple, carbohydrates, such as one or more monosaccharides; disaccharides; oligosaccharides; polysaccharides, such as hemicellulose; and any combination thereof. For example, anionic lignin-based additives may contain 0.01–60% by weight, preferably 0.05–30% by weight, more preferably 0.1–10% by weight, of carbohydrates (such as hemicellulose), calculated based on the total dry weight of the lignin-based additive. The carbohydrate content may depend on the source of the lignin-based additive. For example, polymeric lignin may contain 0.1–5% by weight, typically 0.5–2% by weight, while lignin sulfonates and lignin-carbohydrate complexes may contain 1–15% by weight, typically 1–10% by weight, and lignin obtained by extracting biomass may contain 30–60% by weight of carbohydrates. The carbohydrates in the lignin-based additives are preferably in the form of polysaccharides, such as mannan, galactan, dextran, xylan, rhamnan, and / or arabinogalactan, or fragments or residues thereof; or the carbohydrates may be in the corresponding monosaccharide form. The exact total amount of carbohydrates in anionic lignin-based additives and the relative proportions of various carbohydrates depend on the source of the lignin-based additive, such as the type of wood (e.g., hardwood / softwood), or the method of manufacturing the lignin-based additive.
[0028] According to one embodiment, the anionic lignin-based additive may be a lignin sulfonate or a salt thereof, or a mixture comprising lignin sulfonate and / or its salts. The lignin sulfonates suitable for use in this invention are water-soluble and can be obtained as a byproduct of wood pulp production via a sulfite pulping process. The weight-average molecular weight of the lignin sulfonate is in the range of 3000–50000 g / mol, preferably 5000–25000 g / mol. The charge density of the lignin sulfonate is in the range of -3.0 meq / g to -0.5 meq / g, preferably -2.5 meq / g to -1.0 meq / g, more preferably -2.3 meq / g to -1.3 meq / g, measured in a 200 ppm solution. The lignin sulfonate is typically provided as a dry particulate material with a solids content of >90% by weight, typically 93–98% by weight. The lignin sulfonate or its salt is typically dissolved in water before being used as an anionic lignin-based additive. The resulting lignin sulfonate solution can then be combined with other components of the defoaming composition. Alternatively, lignin sulfonate or its salt can be mixed with other components of the defoaming composition in a dry form, thereby dissolving the lignin sulfonate directly into the defoaming composition and acting as an anionic surfactant therein.
[0029] According to another embodiment, the anionic lignin-based additive may be a polymeric lignin or contain one or more polymeric lignins. The polymeric lignin has a weight-average molecular weight in the range of 10,000–150,000 g / mol, preferably 50,000–130,000 g / mol, more preferably 70,000–120,000 g / mol, and / or a charge density in the range of -2.0 meq / g to -0.5 meq / g, preferably -1.5 meq / g to -1.0 meq / g, measured in a 200 ppm solution. The polymeric lignin can be obtained by the enzymatic oxidation of lignin, preferably derived from biorefining, i.e., energy production from biomass, possibly in conjunction with the co-production of other bio-based products.
[0030] Furthermore, anionic lignin-based additives can be lignin-carbohydrate complexes, or contain one or more lignin-carbohydrate complexes. Anionic lignin-carbohydrate complexes are natural polymer complexes containing lignin and carbohydrates (preferably hemicellulose), covalently bonded together. Therefore, a lignin-carbohydrate complex is a combination of lignin and carbohydrates that are irreversibly bonded to each other into a common structure, wherein lignin and carbohydrates are covalently bonded to each other. For example, lignin or carbohydrates can form the main chain structure of the complex, while another component (carbohydrate or lignin) can form side groups that are covalently bonded to the main chain structure to form a branched structure. Lignin-carbohydrate complexes can be obtained from the side stream of pulping processes of softwood, hardwood, or other lignin-containing cellulose materials, for example, by enzymatic treatment of lignin-carbohydrate materials derived from wood pulping processes. The lignin-carbohydrate complex is anionic, with a weight-average molecular weight ranging from 5,000 to 90,000 g / mol, preferably 8,000 to 50,000 g / mol, and more preferably 10,000 to 45,000 g / mol. The charge density of the lignin-carbohydrate complex ranges from -2.5 meq / g to -0.2 meq / g, preferably -2.4 meq / g to -0.8 meq / g, and more preferably -2.3 meq / g to -0.5 meq / g, measured in a 200 ppm solution. Sometimes the charge density ranges from -2.3 meq / g to -1.5 meq / g.
[0031] Anionic lignin-based additives may also be lignin obtained through the extraction of biomass, such as hot water extraction of spruce sawdust.
[0032] The defoaming composition may contain 0.05–2% by weight, preferably 0.1–1% by weight, more preferably 0.3–0.5% by weight of anionic lignin-based additives, calculated on a dry basis based on the total weight of the defoaming composition.
[0033] In addition to anionic lignin-based additives, the aqueous defoaming composition also contains a nonionic surfactant. The defoaming composition may contain 0.01–2% by weight, preferably 0.02–0.5% by weight, more preferably 0.04–0.2% by weight of a nonionic surfactant, calculated based on the total weight of the defoaming composition. The nonionic surfactant may be selected from ethoxylated C12-C20 fatty alcohols, ethoxylated C12-C20 fatty acids, and any mixtures thereof. Preferably, the nonionic surfactant is an ethoxylated C16-C20 fatty alcohol. Ethoxylated fatty acids or ethoxylated fatty alcohols can be obtained by reacting fatty acids or fatty alcohols with ethylene oxide (EO), preferably with 20–200 EO atoms, more preferably 50–100 EO atoms.
[0034] The defoaming composition further comprises at least one C10-C30 fatty alcohol, preferably at least one C14-C26 fatty alcohol, more preferably at least one C16-C22 fatty alcohol, or any mixture thereof. Therefore, suitable examples of fatty alcohols include, but are not limited to, alcohols comprising 10 to 30 carbon atoms, more specifically 14 to 26 carbon atoms, or even more specifically about 16 to about 22 carbon atoms, and any combination comprising at least one of the aforementioned fatty alcohols. The fatty alcohol can be straight-chain or branched. More specific examples include C14 to C26 straight-chain fatty alcohols, C14 to C26 branched fatty alcohols, and any combination comprising at least one of the aforementioned fatty alcohols. The defoaming composition may comprise 10–40% by weight, preferably 15–25% by weight, more preferably 16–20% by weight, of at least one C10-C30 fatty alcohol, calculated by the total weight of the defoaming composition.
[0035] The aqueous defoaming composition may contain optional oil and / or wax components, for example, in an amount of 0.01–10% by weight, preferably 0.02–7% by weight, more preferably 0.05–4% by weight, based on the total weight of the defoaming composition. Optional wax components may be selected from paraffin wax and microcrystalline wax, and / or optional oil components may be selected from silicone oil, mineral oil, and vegetable oil, preferably vegetable oil.
[0036] Optional oil components may include one or more mineral oils. Oil components may be selected, for example, from synthetic or refined oils, such as kerosene, diesel oil, paraffinic oil, or naphthenic oil, or any mixture thereof, preferably paraffinic oil. Synthetic oil is understood herein as mineral oil produced using the Fischer-Tropsch process or similar polymerization processes. Optional oil components, when containing refined oils, may be cracked mineral oils, solvent-extracted mineral oils, and / or hydrotreated mineral oils. Optional oil components may be, for example, kerosene, diesel oil, paraffinic oil, or naphthenic oil obtained from crude oil through refining and distillation. Paraffinic oil may contain paraffinic hydrocarbons or naphthenic hydrocarbons, or both.
[0037] According to one embodiment of the invention, the defoaming composition is substantially free of mineral oil and / or mineral wax. In the context of this application, mineral oil and mineral wax are understood to be mineral-derived hydrocarbon compounds, such as those obtained from petroleum processing.
[0038] According to one embodiment, the defoaming composition may comprise an oil component, which is silicone oil.
[0039] Optional oil components may be renewable oils, such as vegetable oils. Here, renewable oil is understood to be oil produced from renewable sources (e.g., plants and / or animals). Examples of renewable oils are different types of biodiesel and vegetable oils. Vegetable oils are preferably rapeseed oil or low-erucic acid rapeseed oil, but may also be corn oil, soybean oil, sunflower oil, peanut oil, flaxseed oil, other vegetable oils, or any combination thereof. Vegetable oils are triglycerides (glycerides) of C4-C28, preferably C6-C22 fatty acids having saturated or unsaturated aliphatic chains. Examples of fatty acids found in vegetable oils include, but are not limited to, caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidic acid, and erucic acid.
[0040] Optional wax components (used alone or in combination with oil components) may be selected from paraffin wax (preferably straight-chain unbranched hydrocarbon wax) and microcrystalline wax (typically containing isoparaffin (branched) hydrocarbon wax).
[0041] The defoaming composition may also contain one or more adjuvants selected from thickeners and biocides, wherein the composition preferably contains 0.01–3% by weight, more preferably 0.05–1% by weight, and even more preferably 0.1–0.5% by weight of one or more adjuvants.
[0042] The defoaming composition of the present invention is in the form of an oil-in-water emulsion, wherein oil droplets are dispersed in a continuous aqueous phase (typically water). The defoaming composition may contain 50–90% by weight, preferably 70–87% by weight, more preferably 75–85% by weight of water. The average size of the oil droplets in the defoaming composition may be between 1 and 10 µm, preferably between 3 and 7 µm.
[0043] The defoaming composition can be prepared by known methods for preparing oil / wax-in-water emulsions. A typical process for manufacturing the defoaming composition may include heating a fatty alcohol, optionally an oil / wax component, above their melting point; mixing the molten component with an aqueous phase, wherein a nonionic surfactant, anionic lignin-based additive, and any optional auxiliaries (e.g., thickeners) have previously been dissolved; homogenizing the mixture to obtain an emulsion; and cooling the resulting emulsion.
[0044] According to one embodiment of the invention, the defoaming composition according to the invention can be used in the manufacture of fibrous webs, such as paper, paperboard, or the like, or molded cellulose articles. For example, the defoaming composition can be used to control, reduce, and / or eliminate foam in paper machine applications, paperboard machine applications, pulp screening plant applications, and / or bleaching plant applications. According to one embodiment, the defoaming composition can be used for foam control and / or improved filtration in the production of cellulose fibers (e.g., viscose fiber, cellulose acetate, or water-soluble polymers derived from cellulose, such as cellulose ethers).
[0045] According to one embodiment of the present invention, the defoaming composition according to the invention can be used in water treatment processes. For example, the defoaming composition can be used to control foam generation during wastewater treatment in municipal and commercial settings, such as clarifiers, tanks, outlets, and wastewater ponds.
[0046] The defoaming composition according to the present invention can also be used in the petroleum industry, water treatment, paint or coating manufacturing, food or beverage processing, mining industry, petroleum industry, textile industry, cement industry, agriculture, etc.
[0047] According to one embodiment, the present invention is particularly useful for foam control and / or water filtration improvement in the production of cellulosic fibers (e.g., viscose fiber, cellulose acetate, or water-soluble polymers derived from cellulose, such as cellulose ethers).
[0048] experiment
[0049] The following non-limiting examples describe some embodiments of the present invention.
[0050] Preparation of defoaming composition
[0051] The defoaming composition tested in the examples was an aqueous emulsion of 16.8 wt% C18-C22 fatty alcohol and 2.9 wt% paraffin wax, stabilized by nonionic and anionic surfactants. The defoaming composition was prepared as follows: the fatty alcohol and wax were heated above their melting points, mixed with water in which a nonionic surfactant (0.7 wt%), an anionic surfactant, and a thickener were previously dissolved, homogenized, and the resulting aqueous emulsion was cooled to room temperature (approximately 20°C).
[0052] The defoaming composition used as a reference was prepared as described above. The anionic surfactant was a conventional petroleum-based anionic surfactant.
[0053] The defoaming composition according to the present invention is prepared using the same preparation process and the same amount of the same raw materials as the reference defoaming composition. The only difference is that the conventional petroleum-based anionic surfactant is replaced by an equal weight (dry weight) of anionic lignin-based additives. The properties of the tested anionic lignin-based additives from B to J are shown in Table 1.
[0054] Table 1. Composition and properties of anionic lignin-based additives.
[0055]
[0056] The first series of defoaming compositions A1–J1 were prepared in amounts of 0.75 wt% anionic surfactant (composition A1, reference) or 0.75 wt% anionic lignin-based additive (compositions B1–J1). Weight percentages are given on a dry weight basis, calculated based on the total dry weight of the fatty alcohol and wax. The dry solids content of the defoaming compositions ranges from 20.2 to 20.5 wt%. The average particle size D50, analyzed using a Malvern Mastersizer 2000 particle size analyzer, ranges from 3.5 to 6.0 µm. Defoaming compositions A1–J1 were used to measure emulsion stability and defoaming efficiency.
[0057] The second series of defoaming compositions A2-J2 were prepared in amounts of either 1.5 wt% anionic surfactant (composition A2, reference) or 1.5 wt% anionic lignin-based additive (composition B2-J2). Weight percentages are given on a dry weight basis, calculated based on the total dry weight of the fatty alcohol and wax. The dry solids content of the defoaming compositions ranges from 20.2 to 20.7 wt%. The average particle size D50, analyzed using a Malvern Mastersizer 2000 particle size analyzer, ranges from 3.5 to 6.0 µm. Defoaming compositions A2-J2 were used to measure defoaming efficiency.
[0058] Measurement of emulsion stability
[0059] The stability of the defoaming composition was evaluated by measuring the viscosity of the composition over time at different storage temperatures.
[0060] The viscosity of each defoaming composition was measured over time after storage for 1–2, 7, 14, and 28 days following preparation. The prepared defoaming compositions were divided into three identical samples, and viscosity measurements were performed in parallel at three different storage temperatures: 4°C, 25°C, and 35°C. Viscosities were measured using a Brookfield viscometer with a No. 3 rotor at 60 rpm at room temperature (20°C).
[0061] An increase in viscosity of the defoaming composition during storage indicates that the composition has deteriorated, i.e., the emulsion structure has been partially disrupted by the formation of loose aggregates between particles.
[0062] Measurement of defoaming efficiency
[0063] The efficiency of the defoaming composition was evaluated using a density meter. This device includes a pump, a foaming tank, and a density measuring unit. Defoaming efficiency was measured as follows.
[0064] One liter of process water, preheated to 53°C, is circulated within the system at a constant rate. The density decreases to 910 g / dm³ due to air entrainment (foam formation). 3 Add 10 µl (100% effective content) of the defoaming composition to the process water. Measure the process water density as it rises again over time. The magnitude of this density rise is used to measure the efficiency of the defoaming composition in removing air, reaching a maximum density value. The higher this maximum density value, the lower the air content and the higher the efficiency of the defoamer.
[0065] Example 1
[0066] The storage stability of defoaming compositions B1, C1, and D1 was evaluated at temperatures of 4°C, 25°C, and 35°C, as described above. Defoaming compositions B1, C1, and D1 were prepared using the corresponding anionic lignin-based additives B, C, and D.
[0067] The results are shown in Figure 1 It can be seen that during storage at 25°C and 35°C, the viscosity of defoaming compositions B1, C1, and D1 increased only slightly compared to the reference defoaming composition A1. This indicates that defoaming compositions B1, C1, and D1 exhibit improved stability and can be stored at elevated temperatures for even longer periods. Reference composition A1 already showed a significant increase in viscosity at 25°C. Neither reference composition A1 nor defoaming compositions B1, C1, and D1 showed an increase in viscosity when stored at a low temperature of 4°C, and can be considered stable at this temperature.
[0068] Example 2
[0069] The storage stability of defoaming compositions E1, F1, and G1 was evaluated at temperatures of 4°C, 25°C, and 35°C, as described above. Defoaming compositions E1, F1, and G1 were prepared using the corresponding anionic lignin-based additives E, F, and G.
[0070] The results are shown in Figure 2 As can be seen, during storage at 25°C and 35°C, the viscosity of defoaming compositions E1, F1, and G1 showed only a minimal increase compared to the reference defoaming composition A1. This indicates that defoaming compositions E1, F1, and G1 exhibit improved stability and can be stored at elevated temperatures for even longer periods. Defoaming compositions E1, F1, and G1 did not show an increase in viscosity when stored at a low temperature of 4°C and can be considered stable at that temperature.
[0071] Example 3
[0072] The storage stability of the defoaming compositions H1, I1, and J1 was evaluated at temperatures of 4°C, 25°C, and 35°C, as described above. The defoaming compositions H1, I1, and J1 were prepared using the corresponding anionic lignin-based additives H, I, and J.
[0073] The results are shown in Figure 3 It can be seen that during storage at 25°C and 35°C, the viscosity of defoaming compositions H1, I1, and J1 showed only a minimal, if any, increase compared to the reference defoaming composition A1. This indicates that defoaming compositions H1, I1, and J1 exhibit improved stability and can be stored at elevated temperatures for even longer periods. In this case, defoaming compositions H1, I1, and J1 also did not show an increase in viscosity when stored at a low temperature of 4°C and can be considered stable at that temperature.
[0074] Example 4
[0075] The defoaming efficiency of reference defoaming composition A1 and defoaming compositions B1–J1 was measured as described above. The process water used in the test was white water from the wet end of a paper machine used to manufacture book paper. Reference defoaming composition A1 and defoaming compositions B1–J1 contain the same amount (0.75%) of anionic stabilizer or corresponding anionic lignin-based additive.
[0076] The results are shown in Table 2, which reports the maximum density values achieved by each defoaming composition. Higher maximum density values indicate higher defoaming efficiency. The results show that defoaming compositions containing anionic lignin-based additives exhibit improved or at least similar defoaming performance because they show higher or at least similar maximum density values compared to the reference defoaming composition A1.
[0077] Table 2. Defoaming efficiency of defoaming compositions A1–J1.
[0078]
[0079] Example 5
[0080] The defoaming efficiency of reference defoaming composition A2 and defoaming compositions B2–J2 was measured as described above. The process water used in the tests was white water from the wet end of a paper machine used for manufacturing book paper, which was different from that in Example 4. Reference defoaming compositions A2 and B2–J2 contained the same amount (1.5%) of anionic stabilizer or corresponding anionic lignin-based additives.
[0081] The results are shown in Table 2, which reports the maximum density values achieved by each defoaming composition. Higher maximum density values indicate higher defoaming efficiency. The results show that defoaming compositions B2–J2 containing anionic lignin-based additives exhibit improved defoaming performance because they show higher maximum density values compared to the reference defoaming composition A2. These results confirm the results of Example 4: improved defoaming efficiency can be obtained by using defoaming compositions containing anionic lignin-based additives.
[0082] Table 3. Defoaming efficiency of defoaming compositions A2–J2.
[0083]
[0084] Although the invention has been described with reference to what appears to be the most practical and preferred embodiment, it should be understood that the invention is not limited to the embodiments described above, but is intended to cover various modifications and equivalents within the scope of the appended claims.
Claims
1. An aqueous defoaming composition comprising: - At least one C10-C30 fatty alcohol, - Nonionic surfactants, - Optional wax and / or oil components, and - Anionic lignin-based additives, wherein the anionic lignin-based additives contain 10-100% by weight of lignin, based on the total dry weight of the lignin-based additives.
2. The defoaming composition according to claim 1, characterized in that, The anionic lignin-based additive comprises 20–100% by weight, preferably 65–99.9% by weight, preferably 90–99% by weight, of lignin based on the total dry weight of the lignin-based additive.
3. The defoaming composition according to claim 1 or 2, characterized in that, The anionic lignin-based additive comprises 0.01–60% by weight, preferably 0.05–30% by weight, and more preferably 0.1–10% by weight of carbohydrates, such as hemicellulose, based on the total dry weight of the lignin-based additive.
4. The defoaming composition according to claim 1, 2 or 3, characterized in that, The charge density of the anionic lignin-based additive is -3.0 meq / g to -0.05 meq / g, preferably -2.5 meq / g to -0.5 meq / g, and more preferably -2.0 meq / g to -1.0 meq / g, as measured in a 200 ppm solution.
5. The defoaming composition according to any one of claims 1 to 4, characterized in that, The number average molecular weight of the anionic lignin-based additive is in the range of 5,000 – 150,000 g / mol, preferably 7,000 – 130,000 g / mol, and more preferably 10,000 – 120,000 g / mol.
6. The defoaming composition according to any one of claims 1 to 5, characterized in that, The surface tension of the anionic lignin-based additive is in the range of 40-65 mN / m, preferably 43-60 mN / m, and more preferably 43-55 mN / m.
7. The defoaming composition according to any one of claims 1 to 6, characterized in that, The anionic lignin-based additive is selected from lignin sulfonate, polymeric lignin, lignin-carbohydrate complex, or lignin obtained through biomass extraction.
8. The defoaming composition according to any one of claims 1 to 7, characterized in that, The defoaming composition comprises 0.05–2% by weight, preferably 0.1–1% by weight, more preferably 0.3–0.5% by weight of the anionic lignin-based additive, based on the total weight of the defoaming composition.
9. The defoaming composition according to any one of claims 1 to 8, characterized in that, The defoaming composition comprises: - 10–40% by weight, preferably 15–25% by weight, more preferably 16–20% by weight of at least one C10-C30 fatty alcohol, and / or - 0.01 – 2% by weight, preferably 0.02 – 0.5% by weight, more preferably 0.04 – 0.2% by weight of nonionic surfactant, and / or - 0.01 – 10% by weight, preferably 0.02 – 7% by weight, more preferably 0.05 – 4% by weight of optional wax and / or oil components, The total weight of the defoaming composition.
10. The defoaming composition according to any one of claims 1 to 9, characterized in that, The defoaming composition comprises at least one C14-C26 fatty alcohol, preferably at least one C16-C22 fatty alcohol, or any mixture thereof.
11. The defoaming composition according to any one of claims 1 to 10, characterized in that, The nonionic surfactant is selected from ethoxylated C12-C20 fatty alcohols, ethoxylated C12-C20 fatty acids, and any mixture thereof.
12. The defoaming composition according to any one of claims 1 to 11, characterized in that, The wax component is selected from paraffin wax and microcrystalline wax, and / or the oil component is selected from silicone oil, mineral oil and vegetable oil, preferably vegetable oil.
13. The defoaming composition according to any one of claims 1 to 12, characterized in that, The composition further comprises one or more adjuvants selected from thickeners and biocides, wherein the composition preferably comprises 0.01–3% by weight, more preferably 0.05–1% by weight, and even more preferably 0.1–0.5% by weight of one or more adjuvants.
14. The defoaming composition according to any one of claims 1 to 13, characterized in that, The total dry solids content of the defoaming composition is at least 10% by weight, preferably at least 13% by weight, and more preferably at least 15% by weight.
15. The use of the defoaming composition according to any one of claims 1 to 14 for foam prevention, foam control and / or foam reduction in water treatment processes, in the manufacture of fibrous webs, such as paper, paperboard or the like, or in the manufacture of molded cellulose articles.
